Relationship of Impairment Classification to Injury Incidence in Para Sport Athletes: A Systematic Review - Suci Syafatillah, Shureenzen; Saputra Perdana, Suryo (P3M Universitas 'Aisyiyah Surakarta, 2025)
Background para sport will be divided into a group determined by the type and level of disability of an athlete; impairment classification in the International Paralympic Committee (IPC) is divided into visual, physical, and intellectual impairment. Athletes with impairments increase the risk of events in para-sports. Purpose: The aim was to determine if there is a relationship between impairment classification and the incidence of injury in para-sport athletes. Method: The research is a systematic review following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Data search follows the databases Google Scholar, PubMed, and Scopus using keywords and Boolean search in searching for literature. Result: 10 studies were obtained with publication years between 2016-2022, of which 1 study included reports of injury incidence in athletes with visual, physical, and intellectual impairment, three studies included reports of injury incidence in athletes with visual impairment and physical impairment, three studies included reports of injury incidence in athletes with visual impairment only, and three studies included reports of injury incidence in athletes with physical impairment only. Injury rates in athletes with visual impairment, where the highest population was 267 of elite judokas participating in the IBSA 2018 world judo, 19.1% were injured. Conclusion: This study showed variation in injury incidence based on impairment classification in para-sport athletes, with a high prevalence in athletes with a limb deficiency, neurological impairment, and visual impairment.